И.ЮСУПОВ ШЫҒАРМАЛАРЫНДА ФРАЗЕОЛОГИЗМЛЕР АРҚАЛЫ ПСИХОЛОГИЯЛЫҚ ҲАЛАТТЫҢ БЕРИЛИЎИ - Алламбергенова, Г. (SCIENCE and SOCIETY, 2017)
The article deals with analysing differcut types of psychologicat state through the phraseologisms on the material of the works of I.Ysupov
Keywords: phraselogisms; literary text; compound word; semantic meaning